Interventions to prevent elder abuse in the community: a mixed-methods systematic review - Rute Costa Régis de Sousa; Gleicy Karine Nascimento de Araújo-Monteiro; Rafaella Queiroga Souto; Renata Clemente dos Santos; Cláudia Quézia Amado Monteiro Leal; Neyce de Matos Nascimento (SciELO, 2021)
ABSTRACT Objective: To identify the interventions proposed in the literature aimed at preventing elder abuse among community-residing elders. Method: This was a mixed-methods systematic review that followed the Preferred Reporting Items for Systematic Review and Meta-analysis Protocols checklist. The protocol of this systematic review was registered in the International Prospective Register of Systematic Reviews. We included studies published between January 2004 and December 2019 in the databases: LILACS, IBECS, CUMED, CINAHL, MEDLINE and SciELO. The methodological quality of each study included was performed using the Mixed Methods Appraisal Tool. Results: Seven studies formed the final sample. Two groups emerged after the analyses: the primary level intervention group, which used health education and coexisting elder abuse groups; and the secondary intervention level, focused mostly on the mental health care of victims of elder abuse. Conclusion: There is still a shortage of intervention studies to prevent elder abuse. All the studies selected had a positive outcome, and all interventions can be implemented in nursing care practice.